Apie eksperimentinį investavimo strategijų tyrimą realiose ir virtualiose fi nansų rinkose - Mockus, Jonas; Katin, Igor; Katina, Joana (Information & Media, 2013)
Darbo tikslas yra įvertinti įvairias investavimo strategijas pagal jų pelningumą realiose ir virtualiose fi nansų rinkose. Darbe aprašytas atnaujintas fi nansų rinkos modelis, analizuojami eksperimentinių skaičiavimų rezultatai. On the experimental investigation of investment strategies in the real and virtual fi nancial marketsJonas Mockus, Igor Katin, Joana KatinaSummaryThe optimal fi nancial investment (Portfolio) problem was investigated by leading fi nancial organizations and scientists. The aim of these works was to defi ne the optimal diversifi cation of the assets depending on the acceptable risk level.The aim of the paper is to evaluate different investment strategies in the real and virtual fi nancial markets. This aim is the new element of the proposed simulation system since optimization is performed in the space of investment strategies; both daily and long-term. A number of different investment strategies are presented, including the ones based on the Modern Portfolio Theory (MPT).The simulated investment procedures include different prediction methods. The methods that minimize the mean absolute error (MAE) are added to the traditional ones that minimize the least squares error (MSE). The results of the virtual fi nancial market are compared with historical data.The model is designed as a tool to represent the behavior of an individual investor which wants to predict how the expected profi t depends on different investment strategies using different forecasting methods of real and virtual stocks.